Corrosion protection properties of Janus PTFE coatings in highly corrosive H2SO4 solutions. (October 2022) - Xu, Kaixin; Sun, Wen; Wang, Lida; Yang, Zhengqing; Li, Bohang; Ma, Yunsheng; Zhao, Liqiu; Zhang, Chenghe; Ma, Shiheng; Han, Haoxue; Liu, Guichang
Abstract: To improve the corrosion protection properties of polytetrafluoroethylene (PTFE) in highly corrosive H2 SO4 solutions, Janus PTFE coatings (PDA/PEI@PTFE) were constructed. The modified side is achieved by co-deposition of polydopamine (PDA) and polyethyleneimine (PEI) on the sodium naphthalene etched side of PTFE. It not only has a 5-fold increase in interfacial adhesion with substrates via chemical bonds, but also exhibits improved barrier properties due to the coverage of dense PDA/PEI film, with corresponding corrosion resistance increase by 2–3 orders of magnitude. Meanwhile, the untreated side is hydrophobic pristine PTFE and has good self-cleaning properties and excellent resistance in concentrated H2 SO4 solutions. Highlights: Janus coatings (PDA/PEI@PTFE) were constructed by one side modification. Almost 500% of adhesion enhancement was achieved. The oxygen and water vapor transmission rates decrease by 18.0% and 33.3%. An increase of coating resistance by 2–3 orders of magnitude.